How does the rotational direction of an upwind turbine affect its downwind neighbour?. Issue 2 (1st May 2022) - Englberger, Antonia; Wrba, Linus; Dörnbrack, Andreas; Lundquist, Julie K.
Abstract: Wind-turbine blades rotate in clockwise direction looking downstream on the rotor. During daytime conditions of the atmospheric boundary layer, the rotational direction has no influence on the turbine wakes. In stably stratified conditions occurring during night, the atmospheric inflow is often characterized by a veering inflow describing a clockwise wind direction change with height in the Northern Hemisphere. A changing wind direction with height interacting with the rotor impacts its wake characteristics (wake elongation, width and deflection). We investigate the impact on the turbine performance (streamwise velocity for power, turbulence kinetic energy for loading) of a downwind turbine considering the four possible combinations of rotational directions of two 5 MW NREL rotors by means of large-eddy simulations. A counterclockwise rotating upwind turbine results in a 4.1% increase of the rotor averaged inflow velocity at the downwind rotor in comparison to a common clockwise rotating upwind turbine rotor. In case of two counterclockwise rotating rotors, the increase is 4.5%. This increase in streamwise velocity is accompanied by a 3.7% increase in rotor averaged turbulence kinetic energy. The performance difference of the downwind rotor (+4.8% increase of cumulative power of both wind turbines, if the upwind rotor rotates counterclockwise) results from the rotational direction dependent amplification or weakening of the spanwise and the vertical wind components, which is the result of the superposition of veering inflow and upwind rotor rotation.